Good Governance in Nepal: Legal Provisions and Judicial Praxis - Lamichhane, Bimal Prasad (Journal of Political Science, 2021)
Good governance is about fair application of authority and utilization of resources in implementing coherent governing plan for the best interests and priorities of the people at large. It aims at protection and promotion of rights, welfare and well-being of the citizens through legitimized democratic governance under rule of law. It is avenues for peace, crime control, fairness of public decision with legal certainty and equality. It avails bridled governmental power, qualified administration, and a system of fraud and corruption-free state operation. In Nepali context, The Constitution of Nepal 2015, Commission for the Investigation of Abuse of Authority Act 1991, The Prevention of Corruption Act 2002, Public Procurement Act 2007 and Rules 2008, Good Governance Act 2008, Right to Information Act 2007 and Rules 2009, Local Government Operation Act 2017etc. are the primarily statutory measures to ensure good governance in Nepal. But the legal provisions and practice is not sufficient for ensuring good governance in Nepal. Some remarks on the application of these laws to an end of good governance have been overviewed by apex court in this relation. This article explores the concept as well as elements of good governance and descriptively analyzes various laws, case laws and principles developed by the Supreme Court of Nepal in the issue of good governance. This paper also aims at assessing the strengths and weaknesses of these laws and judicial practices from the internationally accepted good governance norms and principles.